PENINGKATAN HASIL BELAJAR SISWA DENGAN SUB TEMA USAHA PELESTARIAN LINGKUNGAN MENGGUNAKAN MODEL PICTURE AND PICTURE BAGI SISWA KELAS V SD NEGERI 153071 SIBABANGUN 1 - cici krisnawati; Khoiruddin Saleh (Prodi Pendidikan Guru Sekolah Dasar, 2022)
Abstract This study aimed to describe improvement students’ achievement on the topic environmental conservation efforts by using picture and picture learning model at the fifth grade students of SD Negeri 153071 Sibabangun 1. The approach of the research used Class Action Research and the total subject were 23 students. Observation and test were used in collecting the data. The first cycle, students’ achievement showed the mean 43.43 (fair category), 43.48% (10 students) got Minimum Completeness Criteria. Observation sheet showed students’ ability was enough category. Furthermore the second cycle, students’ achievement on the topic environmental conservation efforts showed the mean 82.61 (good category), 87% (20 students) got Minimum Completeness Criteria. Observation sheet showed was good category. It’s concluded picture and picture learning model able to improve students ability on the topic environmental conservation efforts at the fifth grade students of SD Negeri 153071 Sibabangun 1. Keywords: Improvement, students’ achievement, picture and picture learning model Abstrak Penelitian ini bertujuan untuk mendeskripsikan peningkatan prestasi belajar siswa pada topik upaya pelestarian lingkungan dengan menggunakan model pembelajaran picture and picture pada siswa kelas V SD Negeri 153071 Sibabangun 1. Pendekatan penelitian yang digunakan adalah Penelitian Tindakan Kelas dengan jumlah subjek sebanyak 23 siswa. . Observasi dan tes digunakan dalam pengumpulan data. Siklus I, prestasi belajar siswa menunjukkan rata-rata 43,43 (kategori cukup), 43,48% (10 siswa) mendapatkan KKM. Lembar observasi menunjukkan kemampuan siswa dalam kategori cukup. Selanjutnya pada siklus II, prestasi belajar siswa pada topik upaya pelestarian lingkungan menunjukkan rata-rata 82,61 (kategori baik), 87% (20 siswa) mendapatkan KKM. Lembar observasi menunjukkan kategori baik. Disimpulkan model pembelajaran picture and picture mampu meningkatkan kemampuan siswa pada materi upaya pelestarian lingkungan pada siswa kelas V SD Negeri 153071 Sibabangun 1. Kata kunci: Peningkatan, prestasi belajar siswa, model pembelajaran picture and picture